2017
DOI: 10.4103/jispcd.jispcd_496_16
|View full text |Cite
|
Sign up to set email alerts
|

The effects of economic crisis on the demand and supply of the dental services in Greece

Abstract: Objectives:This paper attempts to explore the impact of the economic crisis on the supply and demand of dental care services by listing the changes in costs for dental care as well as by the use of a questionnaire administered to dentists.Materials and Methods:The Health Accounts System, the Household Budget Surveys of the Greek Statistical Authority, and a questionnaire distributed to dentists working as self-employed were used as analysis tools. The survey involved a total of 361 dentists from all the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The model allowed variation in the period of mitigation/suppression policies (thereby reflecting on the short-term impact of Covid-19 on practices) and to simulate longer-term utilization changes. Specifically, a longerterm reduction in out-of-pocket expenses was modelled in a sensitivity analysis, building on data on the alteration of consumption as a consequence of the Greek financial crisis of 2010 [7]. Notably, it is also conceivable that given the expected societal financial losses, contractions in statutory and private health insurance expenditure may occur in the future; this was not reflected on in our analysis.…”
Section: Model and Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model allowed variation in the period of mitigation/suppression policies (thereby reflecting on the short-term impact of Covid-19 on practices) and to simulate longer-term utilization changes. Specifically, a longerterm reduction in out-of-pocket expenses was modelled in a sensitivity analysis, building on data on the alteration of consumption as a consequence of the Greek financial crisis of 2010 [7]. Notably, it is also conceivable that given the expected societal financial losses, contractions in statutory and private health insurance expenditure may occur in the future; this was not reflected on in our analysis.…”
Section: Model and Assumptionmentioning
confidence: 99%
“…This analysis was grounded on data from Greece, as described, showing that dental outof-pocket spending may well contract up to 50 % in all services blocks except those related to pain and emergency treatments. It needs highlighting that the economic crisis in Greece lasted for an extended period; we hence consider this a "worst case scenario" analysis for Germany and the Covid-19 crisis [7]. Note that any further analyses on spending shifts from out-of-pocket to insurances spending were not feasible given the current paucity in data.…”
Section: Model and Assumptionmentioning
confidence: 99%
“…For example, in the case of Cyprus, the only report was that more patients had difficulties financing their health needs 34. However, the most vulnerable social groups suffered devastating consequences in most European countries during the 2008 crisis 1 12 35 36…”
Section: Discussionmentioning
confidence: 99%
“…Brushing the teeth and cleaning the tongue at least twice a day and oral rinsing with antiseptic solutions (like hydrogen peroxide 0.5-1.5%, cetylpyridinium chloride 0.1-1.5% or povidone iodine 0.23-1% [ 85 ], 1.5% hydrogen peroxide, mixture of cetylpyridinium chloride, and povidone iodine) all effectively reduce oral bacterial load [ 86 88 ]. Studies have shown that these products effectively inactivate SARS, MERS, and H1N1 in 1 minute [ 87 90 ]. Finally, oral hygiene should be well improved, especially in ICU and the patients over 70, if anyone seeks to reduce risk of aspiration pneumonia and COVID complications [ 66 ].…”
Section: The Significance Of Oral Hygiene In Covid-19mentioning
confidence: 99%
“…In the meantime, the pandemic has resulted in an economy-wide recession and unemployment, hitting hard the budget constraints of most individuals in the economy. Research has documented that during recessions, for instance, the one in 2008 in the United States or the one in 2012 in Greece, consumers cut nonessential expenditures and increase their precautionary savings to cope with the unknown consequences of the possible long economic meltdown [ 90 ]. The income loss, together with the change in the consumption behavior, reduced the affordability of the nonessential needs and more specifically of the more expensive dental treatment such as implant treatments [ 104 ].…”
Section: Economic Implicationsmentioning
confidence: 99%